E-FILING SEBAGAI PERAN INDONESIA DALAM MEMBERIKAN APRESIASI DAN KONTRIBUSI MENDUKUNG KOMUNITAS ASEAN DALAM KEMUDAHAN PELAYANAN PAJAK - Puspita Anggraini; Feri Prasetyo (Universitas Bina Sarana Informatika, 2014)
E-Filing Tax is a reporting system that is managed by the Direktorat Jendral Pajak to facilitate tax payer in tax reporting. Indonesia as the most populated country in ASEAN needs to participate and play an active role in Providing Appreciation And Contributions which this appreciation can be a service system or procedures that facilitate activities in the service of the population in the country and overseas residents to contribute to support the ASEAN Community, especially in terms of ease tax service. In this study using experimental methods which try using and disseminating the E-Filing system of tax reporting for who do not know in https://efiling.pajak.go.id/index and descriptive analysis where the authors portray and describe some of the activities happened and asked for some users E-Filing in order to conclude whether the E-Filing application beneficial or not.Key words: E-Filling, ASEAN Community, Tax Service